A Poultry Subclinical Necrotic Enteritis Disease Model Based on Natural Clostridium perfringens Uptake - He, Wanwei; Goes, Emanuele C.; Wakaruk, Jeremy; Barreda, Daniel R.; Korver, Douglas R. (Frontiers in Physiology, 2022)
Necrotic enteritis (NE) in poultry is an opportunistic infection caused by Clostridium perfringens. Well-known as a multifactorial disease, NE development is under the influence of a wide range of environmental risk factors that promote proliferation of pathogenic C. perfringens at the expense of non-pathogenic strains. Current in vivo NE challenge models typically incorporate pre-exposure to disease risk factors, in combination to exogenous C. perfringens inoculation. Our goal was to establish a model based on the natural uptake of C. perfringens from the barn environment to produce a subclinical infection. We incorporated access to litter, coccidial exposure, feed composition, and feed withdrawal stress to achieve the commonly observed NE infection peak at 3 weeks post-hatch. NE severity was evaluated based on gut lesion pathology, clinical signs, and mortality rate. Under cage-reared conditions, 15× coccidial vaccine-challenged birds showed overall NE lesion prevalence that was 8-fold higher than 10× coccidial vaccine-challenged birds. NE-associated mortality was observed only in a floor-reared flock after a 15× coccidial vaccine-challenge.